Rancang Bangun Sistem Informasi Wisata Budaya (Studi Kasus Kabupaten Bandung) - Syani, Mamay; Aditya, Fajar; Ahmad Firdaus, Eryan (Jurnal Informatika, 2024)
This Cultural Tourism Information System is constructed with the purpose of seeking information about cultural tourism and cultural objects in the Bandung Regency area. Besides providing cultural tourism information, this cultural tourism information system is employed to discover various cultural tourism events within the Bandung Regency region. Through this research, it is anticipated that it will be beneficial for cultural tourism promotion and aiding in the advancement of local cultural objects in the Bandung Regency. The research method applied is the Rational Unified Process with the utilization of Unified Modeling Language in modeling, while testing is conducted through the BlackBox Testing method. This application is developed using the Laravel Framework and Bootstrap, The results of the implementation show that the overall constructed information system aligns with user requirements. From the conducted User Acceptance Test (UAT), the average parameter results were as follows: design 3.89 (77.9%), features 3.76 (75.3%), and user satisfaction 4.20 (84.2%).